Validation of a claims‐based algorithm to identify cases of ulcerative colitis in Japan - Ogino, Haruei; Morikubo, Hiromu; Fukaura, Keita; Okui, Tasuku; Gardiner, Sean; Sugiyama, Naonobu; Yoshii, Noritoshi; Kawaguchi, Tsutomu; Chen, Haoqian; Nonnenmacher, Edward; Setoguchi, Soko; Nakashima, Naoki; et al. (Journal of gastroenterology and hepatology, 2022)
Background and Aim The prevalence of ulcerative colitis (UC) is increasing in Japan. Validated claims‐based definitions are required to investigate the epidemiology of UC and its treatment and disease course in clinical practice. This study aimed to develop a claims‐based algorithm for UC in Japan. Methods A committee of epidemiologists, gastroenterologists, and internal medicine physicians developed a claims‐based definition for UC, based on diagnostic codes and claims for UC treatments, procedures (cytapheresis), or surgery (postoperative claims). Claims data and medical records for a random sample of 200 cases per site at two large tertiary care academic centers in Japan were used to calculate the positive predictive value (PPV) of the algorithm for three gold standards of diagnosis, defined as physician diagnosis in the medical records, adjudicated cases, or registration in the Japanese Intractable Disease Registry (IDR). Results Overall, 1139 claims‐defined UC cases were identified. Among 393 randomly sampled cases (mean age 44; 48% female), 94% had received ≥ 1 systemic treatment (immunosuppressants, tumor necrosis factor inhibitors, corticosteroids, or antidiarrheals), 7% had cytapheresis, and 7% had postoperative claims. When physician diagnosis was used as a gold standard, PPV was 90.6% (95% confidence interval [CI]: 87.7–93.5). PPV with expert adjudication was also 90.6% (95% CI: 87.7–93.5). PPVs with enrollment in the IDR as gold standard were lower at 41.5% (95% CI: 36.6–46.3) due to incomplete case registration. Conclusions The claims‐based algorithm developed for use in Japan is likely to identify UC cases with high PPV for clinical studies using administrative claims databases.